2018
DOI: 10.1145/3181975
|View full text |Cite
|
Sign up to set email alerts
|

Directing Cinematographic Drones

Abstract: Quadrotor drones equipped with high-quality cameras have rapidly raised as novel, cheap, and stable devices for filmmakers. While professional drone pilots can create aesthetically pleasing videos in short time, the smooth—and cinematographic—control of a camera drone remains challenging for most users, despite recent tools that either automate part of the process or enable the manual design of waypoints to create drone trajectories. This article moves a step further by offering high-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 23 publications
1
58
0
1
Order By: Relevance
“…This environment offers a decent opportunity to evaluate the performance of the trained agent as it has a clear pattern of blocks that the drone can avoid. Our agent performs significantly better than a random policy in the training environment, as well as in the two previously unknown testing environments (Table I) 3 . Our agent is able to achieve all goals that it was supposed to learn:…”
Section: Resultsmentioning
confidence: 82%
“…This environment offers a decent opportunity to evaluate the performance of the trained agent as it has a clear pattern of blocks that the drone can avoid. Our agent performs significantly better than a random policy in the training environment, as well as in the two previously unknown testing environments (Table I) 3 . Our agent is able to achieve all goals that it was supposed to learn:…”
Section: Resultsmentioning
confidence: 82%
“…In particular, we analyze the overhead of the OLSC Solver within the system and establish the feasibility of adopting this enhanced model in a real surveillance system. e prototype we employ for this evaluation leverages typical hardware that can be found at most research labs and is comparable in scale to the experiments reported on closely related systems (Galvane et al 2017;Nägeli et al 2017). In addition, we present a set of large scale simulations that compare the performance of the proposed algorithms against a baseline and establish the sampling heuristic as the method of choice, which we employ on the prototype.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomous cinematography is another application for drones, beyond coverage and tracking, the aesthetic quality plays a key role in viewpoint planning (Joubert et al 2016). Building upon earlier work in virtual cinematography (Lino et al 2011), this exciting line of work has recently been witnessing very interesting developments (Galvane et al 2017;Joubert et al 2015;Nägeli et al 2017). In earlier work, we developed several target coverage algorithms for targets represented as points and deployed them on our testbed (Khan et al 2016;Neishaboori et al 2014a,b;Saeed et al 2014).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…When dealing with dynamic targets, the UAV must anticipate the actor's motion and reason about collisions and occlusions generated by obstacles in potential trajectories. The challenge of visibility has been explored in previous works in varying degrees of obstacle complexity (Bonatti, Ho, Wang, Choudhury, & Scherer, ; Galvane et al, ; Nägeli et al, ; Penin, Giordano, & Chaumette, ).…”
Section: Introductionmentioning
confidence: 99%